2021
DOI: 10.1080/1528008x.2021.1891597
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Multi-dimensional Facets of Perceived Risk in Purchasing Travel Online: A Generational Analysis

Abstract: This paper examines the differences in consumers' risk perception when intending to purchase travel online across Millennials and Baby Boomers. The proposed research model was tested using structural equation modeling. The results show that perceived financial risk, perceived risk privacy, and psychological risk are significant for both Millennials and Baby Boomers. Overall risk was found to have a stronger negative impact on consumers' intention to purchase travel online. Results from this study will be helpf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 94 publications
1
37
0
5
Order By: Relevance
“…Recent studies have employed structural equation modelling (SEM) when analysing data where multiple relationships are tested among constructs [68][69][70]. Partial Least Squares Structural Equation Modelling (PLS-SEM) and covariancebased SEM (CB-SEM) are two variants of SEM that are utilised for analysis [71].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have employed structural equation modelling (SEM) when analysing data where multiple relationships are tested among constructs [68][69][70]. Partial Least Squares Structural Equation Modelling (PLS-SEM) and covariancebased SEM (CB-SEM) are two variants of SEM that are utilised for analysis [71].…”
Section: Discussionmentioning
confidence: 99%
“…The study results also showed that income, education level, and the number of hotel stays affected customers' chosen risk reduction strategies, which provided new evidence to prove the impact of demographic characteristics on risk reduction strategies under the health-related crisis. Therefore, managers need to especially target facets of perceived risk salient with each targeted demographic group by providing different risk reduction strategies [64].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years perceived risk has been widely studied in consumer behavior and attitudes. The literature has focused on online purchasing intentions ( Pelaez et al, 2019 ; Ahmed et al, 2021 ; Jain, 2021 ), buying behavior ( Wai et al, 2019 ; Tobi et al, 2020 ) impulse buying ( Wu et al, 2020 ) travel behavior ( Matiza and Kruger, 2021 ; Sharma et al, 2021 ), and customer loyalty ( Esmaeili et al, 2021 ). Perceived risk has been less studied in the advertising industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chao et al (2020) studied the relationship between perceived privacy risk, psychological resistance and attitude to advertising, and found that perceived privacy risk had no significant effect on advertising attitude; Li et al (2016) and Kurtz et al (2021) studied location-based advertising (LBA) and found that perceived risk has an influence; in short video situational advertising, Zhang Meizhen confirmed the positive effect of perceived risk on psychological resistance and thus on consumers’ willingness to accept through the SOR model. The literature shows that most applications of perceived risk theory focus on the effects on online shopping intention or behavior ( Pelaez et al, 2019 ; Wai et al, 2019 ; Tobi et al, 2020 ; Wu et al, 2020 ; Ahmed et al, 2021 ; Jain, 2021 ; Matiza and Kruger, 2021 ; Sharma et al, 2021 ). There is less research on advertising avoidance in online targeted advertising, and there are inconsistencies in conclusions ( Chen et al, 2019 ; Chao et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%